Self-control, financial literacy and the co-holding puzzle - John Gathergood; Joerg Weber (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2012)
We use UK household survey data incorporating measures of financial literacy and behavioural characteristics to analyse the puzzling co-existence of high cost revolving consumer credit alongside low yield liquid savings in household balance sheets, which we term the 'co-holding puzzle'. Approximately 20% of households in our sample co-hold, on average, 6,500 of revolving consumer credit alongside 8,000 of liquid savings. Co-holders are typically more financially literate, with above average income and education. However, we show co-holding is also associated with impulsive spending behaviour on the part of the household. Our results lend empirical support to theoretical models in which sophisticated households co-hold as a means of managing a self-control problem.
Keywords: D03; D10; D12; E21; 330; Consumer credit; Self-control; Financial literacy